Validasi Status Hara Model Plus One Test pada Latosol dengan Indikator Jagung Manis: Validating Nutrient Status Using Plus One Test Model on Latosol by Maize - Budi Nugroho; Desi Nadalia; Dewi Hanifah (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2020)
The nutrient status evaluation model plus one test is carried out to determine which nutrients are the limiting factor. This model needs to be validated both statistically and agronomically of plant growth and production, so the results can be interpreted appropriately. This study aimed to statistically validate the nutrient status of the model plus one test, evaluate the effect of fertilizer treatment on the growth and production of maize, and the correlation of available soil nutrients with plant nutrients. The experiment was conducted at the Cikabayan Farm, Dramaga Bogor. The experiment used a plus one test treatment design which included: (1) Control, (2) N, (3) N + P, (4) N + P + K, (5) N + P + K + Ca, (6) N + P + K + Ca + Mg, and (7) N + P + K + Ca + Mg + S. Fertilizers used are Urea (N), SP-36 (P), KCl (K), agricultural lime (Ca) ), MgO (Mg), and ZA (S). The environmental design used a randomized block design of 2 replications to obtain 14 experimental units. The results showed that the nutrient of the limiting factor was Ca. This is evident from the results of the variance which showed that the addition of Ca nutrient treatment significantly affected the growth and production of maize. Correlation of exchangeable Ca with crop Ca nutrient content was higher than other nutrients (correlation coefficient / r = 0.75), and classified as very significant. In leaf color reflectant was found that red and green color reflectant was influenced by K nutrient treatment, blue color reflectant by P and Ca nutrients, green and blue color reflectant by Mg nutrient treatment, while blue and red color reflectant by N and S. Nutrient treatment results from nutrient status is used for further fertilization actions.